An integrated electrode based on nanoflakes of MoS2 on carbon cloth for enhanced lithium storage. Issue 16 (5th March 2020) - Guo, Yan; Li, Shuang; Fang, Qiuyue; Zuo, Jialu; Liu, Ming; Zhang, Jun
Abstract : Integrated carbon cloth@MoS2 electrode is fabricated via a facile hydrothermal method as a binder-free anode for lithium-ion batteries. Abstract : Due to its high specific capacity (in theory), molybdenum disulfide (MoS2 ) has been recognized as a plausible substitute in lithium-ion batteries (LIBs). However, it suffers from an inferior electric conductivity and a substantial volume change during Li + insertion/extraction. By using a facile hydrothermal method, a flexible free-standing MoS2 electrode has here been fabricated onto a carbon cloth substrate. The grafting of ultrathin MoS2 nanoflakes onto the carbon cloth framework (forming CC@MoS2 ), was shown to facilitate an improved electron transport, as well as an enhanced Li + transport. As expected, the as-obtained CC@MoS2 electrode was observed to exhibit an excellent lithium storage performance. It delivers a high discharge specific capacity of 2.42 mA h cm −2 at 0.7 mA cm −2 (even after 100 cycles), which is an impressive result.